(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
In the present work, oral dispersible tablets of lafutidine were prepared by direct compression method with view to enhance safety and efficacy of drug molecule as well as to achieve better patient compliance. The objective of this present study is to develop orodispersible tablets of lafutidine using superdisintegrant by simple cost effective direct compression technique which increases the rate of dissolution may leads to increase in oral bio availability. Crospovidone, Sodium Carboxy methyl Cellulose and pregelatinized starch were used as superdisintegrant on account of their well established production technology by direct compression. Lafutidine is a namely developed second generation of histamine H2 receptor antagonist. Lafutidine is having short biological half-life (1.92 ±0 .94 hour),plasma protein binding capability of Lafutidine is 88% and oral bioavailability 22-35%. The prepared tablets were evaluated for thickness, uniformity of weight, content uniformity, hardness, porosity, friability, wetting time, water absorption ratio, In-vitro disintegration time within 18 to 65 sec, and the dissolution profile range in 30 minutes was 88.13% to 97.79%. Drug content was estimated spectrophotometrically at 283nm.DSC & IR spectral analysis were proved that reference Lafutidine and its formulations showed similar absorption bands. It was concluded that superdisintegrants addition technique is favorable for preparing oral dispersible tablets by direct compression method.